Furthering patient adherence: A position paper of the international expert forum on patient adherence based on an internet forum discussion - Heerdink Rob; de Ridder Denise; van Dijk Liset; Sluijs Emmy; van Dulmen Sandra; Bensing Jozien (BMC, 2008)
Abstract Background As the problem of patient non-adherence persists and a solution appears hard to be found, it continues to be important to look for new ways to further the issue. We recently conducted a meta-review of adherence intervention studies which yielded a preliminary agenda for future research, practice and theory development in patient adherence. The objective of the present project was to find out to what extent adherence experts consider this agenda relevant and feasible. Methods The thirty-five corresponding authors of the review studies included in the meta-review were invited to join the International Expert Forum on Patient Adherence and to participate in a four-week web-based focus group discussion. The discussion was triggered by the points on the preliminary agenda presented as propositions to which forum members could react. Two researchers analysed the transcripts and selected relevant phrases. Results Twenty adherence experts participated. Various ideas and viewpoints were raised. After the closure of the web-site, the expert forum was asked to authorize the synthesis of the discussion, to list the propositions in order of priority and to answer a few questions on the use of the web-based focus group as a tool to obtain expert opinions. Their ranking showed that the development of simple interventions is the most promising step to take in fostering patient adherence, preferably within a multidisciplinary setting of medical, pharmaceutical, social and technical science and, not in the least, by incorporating patients' perspectives. Conclusion For enhancing adherence, the development of simple interventions originating from a multidisciplinary perspective including patients' input, appears most promising. Disclosing patients' perspectives requires open communication about patients' expectations, needs and experiences in taking medication and about what might help them to become and remain adherent.